SLOW STEAMING IMPACT ON CONTAINER SHIP’S FUEL CONSUMPTION AND CARBON EMISSION, CASE STUDY: SURABAYA-MAKASSAR ROUTE - Haikal Anjasmara; Muhammad Dhaifullah; Lista Putri Adinda Rahmi (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2024)
This research investigates the implementation and environmental impact of